Pemanfaatan Limbah Cangkang Kerang Hijau (Perna Viridis) Menjadi Kitin Sebagai Biokoagulan Air Sungai - Syamsidar HS; Ramayana Ramayana; Kurnia Ramadani (Al-Kimia, 2017)
This study aims to determine the optimum weight of chitin that used as biocoagulant of river water. The water sample is taken from Kajenjeng river and the chitin used for research are isolated from green mussels (Perna viridis) shell powder through three steps such as deproteination by NaOH 3%, demineralization by HCl 1,25 N and depigmentation by NaOCl 4%. Then, the obtained chitin are contacted into water with variation of 0,25 gram; 0,5 gram; 0,75 gram and 1 gram in an hour. The result showed that optimum weight of chitin for COD determination, total hardness, calcium and turbidity is 0,75 gram, while optimum weight of chitin for magnesium determination is 0,5 gram.